ANALYZING THE POTENTIALS AND CHALLENGES OF DANANTARA IN ADVANCING INDONESIA’S ISLAMIC ECONOMY AND FINANCE - Agustiani, Saputri Handa; Zaliyanti, Rinzani; Danis, Zakia Alfin; Baiti, Baladina Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This article examines the potentials and challenges of Danantara Indonesia (Badan Pengelola Investasi Daya Anagata Nusantara), a newly established sovereign wealth fund designed by the government to manage state-owned strategic assets and promote national economic development, including the strengthening of the Islamic finance ecosystem. With consolidated assets exceeding IDR 14,000 trillion, Danantara is expected to expand access to Islamic financing, support halal infrastructure projects, foster sustainable energy development, and strengthen the agricultural sector. These opportunities are reinforced by Indonesia’s majority Muslim population and the positive growth of the Islamic finance market, which accounted for 10.9% of total national financial assets in 2023. Nevertheless, Danantara’s strategic role faces several obstacles, including regulatory limitations, low levels of Islamic financial literacy, governance risks, and competition with more liquid conventional financial instruments. This study employs a qualitative descriptive approach using library research to explore the dynamics of Danantara’s opportunities and challenges. The findings highlight that Danantara’s success largely depends on transparent governance, the innovation of Islamic investment instruments such as green sukuk, and effective collaboration with Islamic banks and private sector stakeholders. With these strategies, Danantara holds significant potential to enhance the contribution of Islamic finance to the national economy while positioning Indonesia as a global hub for Islamic economic development.